Pengaruh Akses Terhadap Internet, Listrik dan PDRB Per Kapita Terhadap Tingkat Kemiskinan di Nusa Tenggara Timur Tahun 2015-2019 - Nurani Vita Christiani; Anna Ellenora Nainupu (Badan Pusat Statistik Provinsi NTT, 2021)
Reducing the level of poverty is one of the goals of sustainable development at both national and regional scales. The percentage of poor people in NTT since 2015 has continued to decline until 2019, but this decline has not yet met the target in the NTT Province Mid-Term Development Plan. Many studies related to poverty have been conducted with various causes. This research is focused on looking at the effect of access to the internet, electricity in households, and GRDP per capita on poverty. With the fixed effect as the best model, it is found that simultaneously, access to the internet and electricity in households has a negative and significant effect on the poverty level, while the GRDP per capita had a negative but insignificant effect on the poverty level.